(3QSGdI aj Gdhbas - (3eMeO Hf GdHgfSjs
(3ChdgG (B:s
(3GdMeO ddg GdPijSQ GdCMcGe HGdCMcGe def GNJGQ ef GdCfGe hHYO agPg QSGdI eNJUQI efbMI GdMQha ai UMI Gdhba hGddRhe hGdTQhW GdJi HgG Gdhba jOhe aCbhd hdGbhe WQjb Gdhba UMjM HdG s
(3BNQgG (B:s
(3hdPdc bdfG ai LhGH SDGd ai hba MUI hEf Jcdb dg GdeJCed hGYJfi hGddg CYde JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B29s
(3HgG fXGe GdJYbjHIs
(3HBNQgG UhQg aJhi ddeQMhe GHf GdHgfSi ai Gdhba CjVkGs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B266) s
Keywords: (3GdeLGejYs